The Transition Process from Traditional to Digital Financial Management in MSMEs: A Case Study of E-Wallet and Digital Bookkeeping Application Adaptation - Nurhaedah (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This research aims to conduct an in-depth and comprehensive exploration of the complex and non-linear process that occurs when shifting from manual to digital financial management platforms among Micro, Small, and Medium Enterprises (MSMEs) in Makassar City. The study specifically analyzes the sequential adaptation of electronic wallet (e-wallet/QRIS) usage and specialized digital accounting applications. This research addresses three main issues: (1) identifying the key internal and external motivators that initiate the transition, (2) elucidating the specific psycho-managerial phases MSMEs go through during implementation, and (3) analyzing the challenges—particularly cognitive load and financial literacy barriers—that impede the establishment of digital accounting practices. Utilizing a qualitative approach and a multi-case study design, the research involved comprehensive in-depth interviews and observational analysis with 20 owners/managers from various MSME subsectors (culinary, retail, and handicraft) in Makassar over a nine-month period. The findings reveal the transition as proceeding through three distinct yet interconnected phases: Market Pressure and Necessity, Functional Digital Adoption (E-Payment), and Cognitive Institutionalization (Digital Ledger). It was consistently found that limitations in financial literacy—specifically, a low understanding of basic accounting principles—as well as the perceived complexity of application interfaces are the primary hindering factors for full digital integration. Driving factors include market competitiveness, service speed, and the automatic separation of business and personal funds. This study provides important policy implications for creating focused and practical digital literacy programs, contributing significantly to the development of Islamic Education Management by emphasizing the need to integrate digital accounting skills with entrepreneurial ethics to ensure the sustainability and financial transparency of MSMEs